2021
DOI: 10.3390/app11052115
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Extraction Analysis of Arsenic in Soil Samples Collected in an Agricultural Area of Brindisi, Apulia (Italy), in the Proximity of a Coal-Burning Power Plant

Abstract: In order to evaluate the local environmental risk deriving from coal transport and burning, 30 soil samples were collected along the coal conveyor belt and around the coal-burning power plant Federico II of Brindisi (Apulia, southern Italy). Since soil pollution of metals and metalloids is measured not only by their total concentration but also by evaluating their mobility and availability, arsenic sequential extraction, leaching test and speciation analysis were performed. The analytical results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Ammonium oxalate extractions showed that, even in the deeper layers of the sampled sites, a non-negligible quantity of strongly bound or occluded arsenic is present, as already observed in other sites in the area [22], pointing at least partially to a possible natural soil origin.…”
Section: Comparison Of Sitessupporting
confidence: 68%
See 2 more Smart Citations
“…Ammonium oxalate extractions showed that, even in the deeper layers of the sampled sites, a non-negligible quantity of strongly bound or occluded arsenic is present, as already observed in other sites in the area [22], pointing at least partially to a possible natural soil origin.…”
Section: Comparison Of Sitessupporting
confidence: 68%
“…Obviously the collection of this type of data would have required a much more extensive approach. Nevertheless, the speciation analyses confirmed that most As occurs as relatively immobile or slowly exchangeable forms, suggesting that it is a naturally occurring component of the soil in the area [22]. In fact, As is generally associated with sulfide minerals, and its mobility and availability in soils are strictly related to pH, redox potential, ionic composition, and mineral type.…”
Section: Comparison Of Sitesmentioning
confidence: 87%
See 1 more Smart Citation
“…Operationally defined fractionation of elements in various environmental samples has been conducted using sequential leaching methods. Examples are river sediments [13][14][15], soils [16][17][18], coal ash [4,19,20], green liquor dregs [21], black shale [22], phosphogypsum [23], sewage sludges [24][25][26], and mine wastes [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical sequential extraction has some problems related to the solubilized phase and/or the extracted fraction, in addition to the possibility of losing soil/sediment mass during the sequential extraction (Martin et al, 1987;Migoni et al, 2021). Non-destructive analyzes, such as those based on synchrotron radiation (Lombi and Susini, 2009) have been used as an alternative for sequential extraction.…”
Section: Introductionmentioning
confidence: 99%